2010
DOI: 10.1007/s10765-010-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Realization of Zinc Point and the Zinc-Point Cell Comparison

Abstract: Continuing our study on aluminum, tin, and silver points, a study on the realization of the zinc point was conducted. Zinc-point cells were newly fabricated using 6N-nominal grade zinc samples, impurity elements of which were analyzed extensively based on glow-discharge mass spectrometry (GDMS). The present paper reports the temperature measurements done using the newly fabricated cells during the zinc freezing process, under which the zinc fixed point is defined, and the analysis of the freezing curve obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…In our comparison that involves various combinations of zinc-point cells and identical zinc-point furnaces [8], we found that temperatures measured by cells under comparison show trends to arrive at one common point on an imaginary axis 1/F = 0. Temperatures shown in Fig.…”
Section: Cell Comparisonsmentioning
confidence: 83%
“…In our comparison that involves various combinations of zinc-point cells and identical zinc-point furnaces [8], we found that temperatures measured by cells under comparison show trends to arrive at one common point on an imaginary axis 1/F = 0. Temperatures shown in Fig.…”
Section: Cell Comparisonsmentioning
confidence: 83%
“…Since the main uncertainty of the fixed point temperature is caused by the influence of the impurities, its estimation based on impurities diffusion processes in a metal seems to be doubtful. The process of irregular growth of dendrites in liquid metal can result in a nonuniform impurities distribution after crystallization [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…It is the practice to consider that in case all recommended conditions of the fixed point realization are fulfilled, the outer interface moves from the walls of the crucible to its center, the inner interface moves from the thermometer well to the crucible walls, and diffusion process results in formation of heterogeneous distribution over the crucible radius. Using the model accepted for the process of crystallization in a cell, it is difficult to explain a significant nonuniformity of impurities distribution over a metal height, which has been revealed in [4,5]. The understanding of the processes which cause a deviation of the real crystallization process from the model with a planar interface is important for evaluating the uncertainties of a measurement result due to the influence of impurities.…”
Section: Introductionmentioning
confidence: 99%
“…The metal fixed points are operated at higher temperature than ambient conditions such that it's difficult to reduce the heat fluxes below a few watts as the thermal resistance between the fixed-point cells and furnaces are low. The usual solution is to establish two solid-liquid interfaces in the fixed-point cell; however some publications manifested nice realizations with single solid-liquid interfaces by improving in the design of the furnace and in the control system [1][2][3][4]. It allows the heater power measurements during the phase change of fixed-point cells such that F can be accurately determined.…”
Section: Introductionmentioning
confidence: 99%
“…With a view to evaluating the influence of impurity on the temperatures of the solid-liquid phase transformation of high-purity substances in metal fixed-point cells, two methods have been recommended [4]. The sum of individual estimates (SIE) method leads to a temperature correction when detailed information about impurities is available, while the overall maximum estimate (OME) method is to estimate the overall impurity using the first cryoscopic constant and expressed as a mole fraction.…”
Section: Introductionmentioning
confidence: 99%